Measurement of AI3, AI4, and DS4 IT Process Maturity Using the Cobit 4.1 Framework at KOMINFO Bantul - Muhammad, Goldi Mahardika; Noto Susanto, Chayadi Oktomy; Kurnianti, Aprilia (Emerging Information Science and Technology, 2020)
This research discusses the condition of information technology at KOMINFO (DISKOMINFO) Bantul governance. This study aims to discover where has KOMINFO applied information technology governance properly. This research focuses only on IT processes. Only the AI3 IT process discussed how to generate and maintain the IT infrastructure. AI4 IT process discussed how to enable and use the IT infrastructure, and the last is the DS4 IT process that discussed how to ensure sustainable services. A questionnaire, an interview with employees of KOMINFO Bantul, and documentation were utilized to collect data. Data processing results were used to determine the maturity level of information technology governance at KOMINFO Bantul. After knowing the maturity level of the IT processes, then it was analyzed to measure the alignment between the TKTI current condition with the TKTI condition equipped with the COBIT framework.